Teacher agency and professional learning communities; what can Learning Rounds in Scotland teach us?. Issue 3 (27th May 2017) - Philpott, Carey; Oates, Catriona
Abstract : Recently there has been growth in researching teacher agency. Some research has considered the relationship between teacher agency and professional learning. Similarly, there has been growing interest in professional learning communities as resources for professional learning. Connections have been made between professional learning communities and teacher agency, with professional learning communities seen as an affordance for the exercise of teacher agency. However, it has also been argued that there is little detailed evidence of what happens inside professional learning communities or of teacher agency in action. The research reported here focuses on a form of professional learning community from Scotland: Learning Rounds. It uses data from transcripts of post-classroom observation conversations to consider the extent to which Learning Rounds provide an affordance for teacher agency and the extent to which that affordance is utilised. This research makes a contribution in three ways: adding to an empirical understanding of what happens in professional learning communities; understanding how teacher agency is (or is not) exercised in practice; and considering what factors might affect the utilisation (or otherwise) of affordances for teacher agency. The article concludes with several recommendations for developing effective professional learning communities as an affordance for teacher agency.